Ivan Illich’s Medical Nemesis and the ‘age of the show’: On the Expropriation of Death - Babich, Babette E. (Nursing philosophy, 2018)
What Ivan Illich regarded in his Medical Nemesis as the ‘expropriation of health’ takes place on the surfaces and in the spaces of the screens all around us, including our cell phones but also the patient monitors and (increasingly) the iPads that intervene between nurse and patient. To explore what Illich called the ‘age of the show’, this essay uses film examples, like Creed and the controversial documentary Vaxxed, and the television series Nurse Jackie. Rocky’s cancer in his last film (submitting to chemo to ‘fight’ cancer) highlights what Illich along with Petr Skrabanek called the ‘expropriation of death’. In contrast to what Illich denotes as ‘Umsonstigkeit’ - grace or gift, given undeservedly, i.e., gratuitously - medical science tends to be tempted by what Illich terms scientistic ‘black magic’, taking over (expropriating) the life and the death of the patient in increasingly technological ways, a point underscored in the concluding section on the commercial prospects of xenotransplants using factory farm or mass-produced human-pig mosaics or chimeras.